Business plan for CityTRAXX - Han, Derek Chong Hao (2014)
The present electronic information provision industry has not progressed as tremendous as the advancement of the computer. We have come up with a new concept of operating a system, similar to the ones already in the market, that would quicken this hold-up. The system is called CityTRAXX. The purpose of this applied research project is to develop a winning business plan for our conceptual product CityTRAXX. The applied research project focused on comparisons with the various sources of funds available, namely venture capital companies, banks, and governmental agencies. Literature search showed that venture capitalists are the better people to approach for new ventures requiring huge start-up amounts. In addition, we also did our own survey to determine whether there is a market for CityTRAXX. Results showed that the public is favourable for our system and we also found out the general price level that they are willing to pay. We have tailored this business plan in favour of the venture capital companies and following the format would greatly increase any entrepreneur's probability of obtaining funds for his or her new venture.